Kontribusi Timbal Balik Kerinci dan Indrapura dalam Dunia Perdagangan Abad 18-20 M (Studi Kasus: Komoditi Kerinci dan Indrapura) - ZE, Deki Syaputra (Jurnal Ilmiah Dikdaya, 2022)
In writing history, especially the history of trade, historical reviewers are often only stuck on the events of the deck of VOC ships on the coast. Sometimes the role of local traders and rulers often escapes the attention of the reviewers, moreover, the role of the interior to trade in the coastal area is very rarely touched. As if the interior does not play a role or be taken into account in the world of trade on the coast, but in fact the interior plays a role as a driving force for the economy/trade on the coast. One example is between Kerinci and Indrapura, the hinterland and coastal areas or trading ports that need each other. Therefore, this study will look at how the mutual contribution of Kerinci and Indrapura from the 18th to the 20th century AD in trading commodities. This study uses historical research methods starting from source collection, source criticism, interpretation to historiography using a multi-dimensional and multi-causal approach, presenting research results in the form of descriptive analysis. The AlamKerinci area as the hinterland and Jambi and Indrapura position as coastal areas and port cities, making the concept used is hinterland-port cities (inland with port cities) as the object of this research. The sources used are written sources in the form of books, archives and ancient manuscripts and other important documents.